2012
DOI: 10.3892/ijo.2012.1535
|View full text |Cite
|
Sign up to set email alerts
|

MiR-23a regulates TGF-β-induced epithelial-mesenchymal transition by targeting E-cadherin in lung cancer cells

Abstract: Transforming growth factor-β (TGF-β)-induced epithelial-mesenchymal transition (EMT) has been shown to be related to the pathogenesis of various diseases including lung cancer. Recently, microRNAs (miRNA) have been recognized as a new class of genes involved in human tumorigenesis. MiR-23a/24/27a is a miRNA cluster located in chromosome 19p13.12, which can function as an oncogene in several human cancers. In this study, we analyzed miR-23a/24/27a expression in 10 non-small cell cancer (NSCLC) cell lines by rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
121
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 41 publications
3
121
0
Order By: Relevance
“…f Thirty minutes after incubated with EtBr, the content of LDH in the culture medium was measured as described in "Materials and methods". Values are means±SE (n=4) PC-9 cells is low [25], the Smad-dependent canonical TGF-β1 signaling pathway might be aberrant in PC-9 cells. We also found that the motile activity of PC-9 cells was suppressed by treatment with ecto-nucleotidase or P2X7 antagonists, suggesting that constitutive activation of P2X7 receptor is involved in the motility of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…f Thirty minutes after incubated with EtBr, the content of LDH in the culture medium was measured as described in "Materials and methods". Values are means±SE (n=4) PC-9 cells is low [25], the Smad-dependent canonical TGF-β1 signaling pathway might be aberrant in PC-9 cells. We also found that the motile activity of PC-9 cells was suppressed by treatment with ecto-nucleotidase or P2X7 antagonists, suggesting that constitutive activation of P2X7 receptor is involved in the motility of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…miR-24 also regulates the processing of the pre-TGF-b1 isoform via furin (Luna et al, 2011), such that reduced miR-24 expression would lead to elevated furin-mediated TGF-b1 processing. TGF-b1 induces miR-23 but not miR-24 expression in A549 cells and suppresses miR-24 in myocytes, both in a Smad3-dependent manner (Cao et al, 2012).In summary, this study identifies for the first time, to the best of our knowledge, a mechanism by which RSV NS1 suppresses the expression of miR-24 and induces KLF6 expression to promote TGF-b-mediated cell cycle arrest and RSV replication. miR-24 may prove to be a viable antiviral target, as the induction of miR-24 may overcome RSV-induced cell cycle arrest and inhibition of apoptosis, thus improving viral clearance from infected cells.…”
mentioning
confidence: 63%
“…miR-24 also regulates the processing of the pre-TGF-b1 isoform via furin (Luna et al, 2011), such that reduced miR-24 expression would lead to elevated furin-mediated TGF-b1 processing. TGF-b1 induces miR-23 but not miR-24 expression in A549 cells and suppresses miR-24 in myocytes, both in a Smad3-dependent manner (Cao et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations